(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This paper examines how alternate realities function as hyperreal spaces in Matt Haig’s The Midnight Library, analyzed through a postmodern theoretical lens. Drawing on Jean Baudrillard’s concept of hyperreality, the study demonstrates how the novel destabilizes fixed notions of authenticity by collapsing the boundaries between lived reality and simulated possibilities. Nora Seed’s traversal of multiple coexisting lives is positioned as a narrative exploration of existential crisis, regret, and the search for meaning, revealing how emotional experiences can render simulated worlds indistinguishable from the real. The analysis further situates the novel within postmodern discourse, highlighting its engagement with narrative fragmentation, metafiction, and the plurality of subjective truths. By mapping hyperreality onto Nora’s existential transformation, this paper establishes The Midnight Library as a contemporary text that meaningfully intersects with postmodern thought, offering new insight into how fiction represents the fluidity of identity and reality in the twenty-first century.